La lúdica y su importancia en el desarrollo socio- afectivo - Toapanta Paredes, Gabriela Natali (2017)
The research project presented about "The playful and its importance in the socio-affective development" It was developed with the objective of diagnosis the use of leisure activities to enhance the skills in the socio-affective area in Children of nursery education, using a methodology with a mixed approach that allows the broad theoretical description on the problem of socio-affective development and the application of instruments such as; the survey, interview and observation sheet to quantify trends and perspectives of the educational people on the socio-affective development of children, complemented by bibliographical-documentary and field research that allow to gather the theoretical foundations on the ludic activities and the socioeconomic development determining the benefits and the use of these activities, at nursery education. The research project benefited 26 children of Nursery education, their teacher and parents at "Victoria Vásconez Cuvi" Educational Unit Latacunga city, Cotopaxi province, since it determined the feasibility and importance of including playful activities in education to enhance the children´s emotional social skills....